Ecological drivers of plant communities diversity and structure along pedoenvironmental gradients in Maritime Antarctica - Schmitz, Daniela (2019)
In landscape scale, the availability of ice-free areas determines the distribution of terrestrial vegetation in Antarctica. The vegetation is predominantly composed of bryophytes and lichens that develops in plains, terraces, slopes, on rocks and soils at different stages of development, in the islands and coastal regions of Antarctica. The distribution and structure of vegetation in Antarctic Maritime is due to factors still little elucidated. Soil characteristics can be an important factor in the assembly of plant communities, as well as their dynamics and development. Changes in landscape and plant communities are responses to climate change in these extremely sensitive areas. The study aimed was to analyze the changes in richness, composition and vegetation cover along a pedoenvironmental gradient in three distinct islands of Maritime Antarctica, evaluating the ecological standards of the diversity of species of non vascular plants. Also, analyzing the changes in the thermal regimes of the active layer in three criossolos with contrasting plant communities and different coverage patterns. This evaluation was conducted in three distinct islands of the South Shetland archipelago: Nelson, Half Moon and Elephant. For this, vegetation sampling was performed in distinct areas that form a pedoenvironmental gradient. The vegetation communities of each pedoambiente were sampled using around 20 plots using the phytosociological method of Braun-Blanquet. In each plot a soil sample was collected for chemical and physical analysis. In order to analyze the thermal regime of the active layer, three areas were selected on Elefante Island, with different vegetation cover and open soil profiles for the installation of temperature and moisture soil sensors at different depths, as well as an air temperature sensor. Data collection was done every hour and stored in a CR3000 datalogger for a period of two years. Our results show that the richness and composition of species as well as the vegetation cover varied along the pedoenvironmental gradient. However, differences in species composition were not as marked as expected, showing high degrees of similarity between different pedoenvironments. Our models have shown that different predictors have effects on species composition in the different islands studied, presuming that there is no specific pattern for the distribution of species molded by a pedoenvironmental gradient. It allows us to conclude that pedoenvironmental filtering ixcan determine different patterns of diversity and structure of non-vascular plant communities through different processes in each of the islands. Also, there were significant differences between air and soil temperature, due to the vegetation cover effect, but no effect was observed on soil moisture.